Considerations for Meeting Students' Mental Health Needs at a U.S. University During the COVID-19 Pandemic: A Qualitative Study - Kaur, Jessalyn; Chow, Eva; Ravenhurst, Johanna; Snyder, Teah; Pennell, Sheila; Lover, Andrew A.; Goff, Sarah L. (Frontiers in Public Health, 2022)
Objective To better understand the potential ongoing effects of the COVID-19 pandemic on U.S. university students' mental health and to generate hypotheses as to how universities may best meet students' mental health needs. Participants Students at a large public university in the United States. Methods Students were invited via email to participate in either interviews or focus groups regarding their COVID-19 pandemic experiences, including mental health impacts. Recruitment took place in two waves. Sessions were led by student members of the research team and took place via video conference between December 2020 and June 2021. Interviews were audio-recorded and transcribed via Zoom and manually edited and de-identified by the research team. Interview data were analyzed deductively and inductively using a modified grounded theory approach. Results A total of 40 undergraduate and graduate students took part in the study. Major themes included: (1) Overall impact of the pandemic on mental health; (2) Sources of pandemic stress/mental health impacts; (3) Subsequent coping strategies; and (4) Suggestions for improving university support for student mental health. Subthemes were identified within each major theme. Students reported substantial anxiety and other mental health impacts and felt improvements in communication and access to mental health resources could better support students. Conclusions This study provides context for the ways in which the COVID-19 pandemic may be continuing to impact mental health in a north-American university setting and identifies suggestions for potential interventions that future studies may test for effectiveness.